Physical properties of thin ZnO layers - Bulanyi, M. F.; Kovalenko, O. V.; Omelchuk, A. R.; Polozov, K. Yu.; Skuratovskaya, O. V. (Видавництво Львівської політехніки, 2012)
It has been investigations the photoluminescence spectra, form of the surface and x-ray diffraction analyzing of ZnO epitaxial layers grown by VPE and MOCVD technology.
Keywords: zinc oxide; photoluminescence; x-ray diffraction analyzing; morphology of surface